Design and Development of a Website-Based Employee Recruitment Application for the Construction Industry: Rancang Bangun Aplikasi Rekrutmen Karyawan Industri Konstruksi Berbasis Website - Andreka, Frizky; Putri Amelia (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
The growth of the construction industry in Indonesia demands a transformation of the technology-based recruitment system to improve efficiency and transparency. PT. Songgo Jati Baru experienced operational constraints due to the manual recruitment process that was prone to delays and human error. To overcome this, a recruitment application was developed to automate the candidate selection process. The system development was carried out using the Agile method iteratively, with UML modeling and Black Box testing. The implementation results were able to accelerate the selection process, reduce errors, and increase transparency. In addition, the application allows the compilation of a candidate database based on technical competency and work experience, which supports the company's long-term recruitment strategy. This study recommends the adoption of a digital recruitment system as a strategic innovation in improving the quality of human resources in the construction sector, in line with the direction of national digital transformation.